Thismia malayana (Thismiaceae), a new mycoheterotrophic species from Peninsular Malaysia - Mat Yunoh Siti-Munirah; Chin Hardy-Adrian; Sharipudin Mohamad-Shafiq; Zainuddin Irwan-Syah; Abd Halim Hamidi (PhytoKeys, 2024)
A new species of the mycoheterotrophic genus Thismia from Malaysia is described and illustrated. Thismia malayana introduced here was found in two localities: in the lowlands of Gunung Angsi Forest Reserve, Negeri Sembilan, and in the hilly dipterocarp forests of Gunung Benom in Tengku Hassanal Wildlife Reserve, Pahang. Thismia malayana falls into the section Thismia subsect. Odoardoa, as it has creeping vermiform roots and free equal tepals. It is characterised by the following taxonomically important features: a sepia-brown, urceolate-curved floral tube, free equal tepals with terminal appendages, prominent bright yellow annulus and bright violet-blue stamens each bearing five appendages (one pair of club-shaped inwards-pointing, one pair of acute outwards-pointing, and one central appendage). According to the categories and criteria of the IUCN Red List, T. malayana is provisionally classified as Vulnerable.